Memórias de leituras de idosos da UATI/UEFS: ressignificando suas histórias - Lima, Eliana Carlota Mota Marques (2016)
Despite of the growth of actions and studies focused on older people in recent decades, as the progressive aging of the population, there is still a weakness of research in relation to elderly reading stories, as well as about the importance of remembering those stories. This way, this essay has the purpose to identify, reconstruct and record the individual memories of the elderly, whose outlined problems were the investigation of reading stories of these subjects related to their life stories. This research sought to understand how the elderly have re-meant their lives by reference to the readings done. Participants in the research were five subjects who attend to the workshop Memories and readings from Universidade Aberta à Terceira Idade at Universidade Estadual de Feira de Santana – Bahia. This paper analyzes issues related to family background, childhood, school, work, reader trajectory and reflects on the reinterpretation of life of the elderly based on their reading memories. The research follows a qualitative descriptive nature, with the methodological basis the story of life, using the interview as data collection tool, in order to get as much as possible from the memories of those involved. The data were analyzed through the light of cultural history, the history of reading and remembering. Therefore, it sought to support the ideas of Peter Burke (2008), Roger Chartier (2004, 2009, 2015) and Ecléa Bosi (1994, 2013), among other scholars. By analyzing the memories of older people, it is possible to draw a profile of these readers, noting its varied modes of interaction with reading at different periods of their lives. The result of the work brings out the personal stories and reading memories of older people, revealing the importance of the act of remembering these subjects not only relive moments, events, memories from the past, but also they can redo themselves, they can re-mean themselves and then they can enjoy their aging process healthily.